Images of Olsztyn recorded in the latest prose of writers born in 70s and 80s in relation with past and future - Chłosta-Zielonka, Joanna (Prace Literaturoznawcze, 2018)
The aim of the paper is to point at the way in which contemporary writers use collective memory connected with Olsztyn, the town in which traces of the past can be seen in architectural and cultural landscape. Quoting after Elżbieta Rybicka definition of the memorials by the French researcher Pierre’a Nora, it can be assumed that memories concerning the past are kept by topographic places and monuments: statues, cemeteries and architecture. In the generation of people born in 70s won strategy which is called by Bartosz Korzeniewski ”de-browning” of history. The authors referred to the sings of the town’s past very critically. It was not until the first decade of the 21st century when the perspective of the description of Olsztyn’s everyday life changed. It can be noticed in the crime stories written by Tomasz Białkowski, short story by Michał Kotliński and crime story Rage by Zygmunt Miłoszewski.